A recyclable ionogel with high mechanical robustness based on covalent adaptable networks - Fan, Xiaotong (2024)
Ionogels are an emerging class of soft materials for flexible electronics, with high ionic conductivity, low volatility, and mechanical stretchability. Recyclable ionogels are recently developed to address the sustainability crisis of current electronics, through the introduction of non-covalent bonds. However, this strategy sacrifices mechanical robustness and chemical stability, severely diminishing the potential for practical application. Here, covalent adaptable networks (CANs) are incorporated into ionogels, where dynamic covalent crosslinks endow high strength (11.3 MPa tensile strength), stretchability (2396% elongation at break), elasticity (energy loss coefficient of 0.055 at 100% strain), and durability (5000 cycles of 150% strain). The reversible nature of CANs allows the ionogel to be closed-loop recyclable for up to ten times. Additionally, the ionogel is toughened by physical crosslinks between conducting ions and polymer networks, breaking the common dilemma in enhancing mechanical properties and electrical conductivity. The ionogel demonstrates robust strain sensing performance under harsh mechanical treatments and is applied for reconfigurable multimodal sensing based on its recyclability. This study provides insights into improving the mechanical and electrical properties of ionogels toward functionally reliable and environmentally sustainable bioelectronics.